Body, self, other : the phenomenology of social encounters - Dolezal, Luna; Petherbridge, Danielle (Suny Press, 2017)
Examines the lived experience of social encounters drawing on phenomenological insights.
Keywords: Interpersonal relations -- Philosophy.; Other (Philosophy); Phenomenology.; Altérité.; Phénoménologie.; phenomenology.; PHILOSOPHY / Movements / Phenomenology; Interpersonal relations -- Philosophy; Phenomenology